2010
DOI: 10.1101/gad.1914110
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of HDA6-mediated rRNA gene silencing: suppression of intergenic Pol II transcription and differential effects on maintenance versus siRNA-directed cytosine methylation

Abstract: The Arabidopsis histone deacetylase HDA6 is required to silence transgenes, transposons, and ribosomal RNA (rRNA) genes subjected to nucleolar dominance in genetic hybrids. In nonhybrid Arabidopsis thaliana, we show that a class of 45S rRNA gene variants that is normally inactivated during development fails to be silenced in hda6 mutants. In these mutants, symmetric cytosine methylation at CG and CHG motifs is reduced, and spurious RNA polymerase II (Pol II) transcription occurs throughout the intergenic space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
204
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 152 publications
(222 citation statements)
references
References 57 publications
(67 reference statements)
11
204
0
Order By: Relevance
“…Genome-wide gene expression analysis using the Affymetrix GeneChip indicates that down-regulation of HDA6 affected genes involved in a variety of biological processes. In addition to genes involved in flowering, genes involved in gene silencing and stress responses were also affected in hda6 mutants, supporting multiple functions of HDA6 (Aufsatz et al, 2007;Wu et al, 2008;Chen et al, 2010;Earley et al, 2010). We found that the expression of two genes encoding AGO proteins, AGO5 and AGO3, was up-regulated in hda6 mutants.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…Genome-wide gene expression analysis using the Affymetrix GeneChip indicates that down-regulation of HDA6 affected genes involved in a variety of biological processes. In addition to genes involved in flowering, genes involved in gene silencing and stress responses were also affected in hda6 mutants, supporting multiple functions of HDA6 (Aufsatz et al, 2007;Wu et al, 2008;Chen et al, 2010;Earley et al, 2010). We found that the expression of two genes encoding AGO proteins, AGO5 and AGO3, was up-regulated in hda6 mutants.…”
mentioning
confidence: 63%
“…By using microarray analysis, two additional MADS box genes, AGL37 and AT5G59930, were also identified to be up-regulated and hyperacetylated in axe1-5 plants. Since HDA6 is a trichostain A-sensitive histone deacetylase capable of removing acetyl groups from multiple Lys residues of histones (Earley et al, 2006(Earley et al, , 2010, HDA6 may repress FLC as well as other MADS box genes through deacetylating their chromatin. ChIP analysis indicated that HDA6 bound directly to the promoters of FLC, MAF4, and AT5G59930, suggesting that they may be the direct targets of HDA6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HISTONE DEACETYLASE 6 (HDA6) is required for uniparental rRNA gene silencing in hybrid Arabidopsis suecica and for developmentally regulated silencing of variant 1 rRNA genes in nonhybrid A. thaliana (Earley et al 2006(Earley et al , 2010. HDA6 localizes throughout nuclei, including the nucleolus (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All subtypes are expressed immediately following germination, but by ;10 d of seedling growth, the variant 1 subtype (Fig. 1A), accounting for ;50% of all rRNA genes, is silenced via epigenetic mechanisms that include changes in DNA methylation and histone modification (Earley et al 2006(Earley et al , 2010Pontvianne et al 2010Pontvianne et al , 2012. Chromatin modifications mediate rRNA gene dosage control in yeast, mouse, and human cells as well (Sandmeier et al 2002;McStay and Grummt 2008;Grummt and Langst 2013).…”
mentioning
confidence: 99%